TREATMENT OF RHEUMATIC DISEASES INTERRELATION OF SELECTIVE NON-STEROIDAL ANTIINFLAMMATORY DRUG CELEBREX (CELECOXIB) AND INHIBITOR OF ENZYME WITH APF ENAP (ENALAPR1L) IN PATIENTS WITH RHEUMATIC DISEASES AND CONCOMITANT ARTERIAL HYPERTENSION - Yu. V. Mouraviev; T N Tsapina; L N Kashnikova (Научно-практическая ревматология)
Objective. To assess the effect of selective NSAID Celecoxib on the indices of arterial pressure in RD pts with concomitant arterial hypertension and taking Enalapril. Material and methods. 10 pts (5-RA, 5 - OA) had daily monitoring of arterial pressure, assessment of renal functions against background of Celecoxib and Enalaplir therapy. Results. During combined therapy by Celecoxib and Enalapril arterial pressure, levels of creatinine and blood urine, minute diuresis, speed of glomerulal filtration was not practically changed. Nevertheless in 3 pts considerable increase of arterial pressure was observed. Conclusion. The majority of pts did not demonstrate negative Celecoxib effect on hypotensive Enalapril properties, the third of pts demonstrated increase of daily monitoring of arterial pressure, no negative effect on renal function was found.